Ancient temple ornaments in Latvia - Ciglis, Jānis (Archaeologia Lituana, 2011)
It is a little bit curious, that at the end of the Late Bronze Age and the Early or Pre-Roman Iron Age these temple ornaments were the most common metal ornament type in the territory of Latvia, but later periods these ornaments almost disappeared.The Pre-Roman Iron Age temple ornaments can be divided into three groups. The most wide-spread temple ornaments were plain spiral temple ornaments (first group) and ornaments with a spiral middle part and spoon-shaped ends (second group). The third group consists of ornaments made of thin bronze wire rings with beads and pendants.